Commercial banks lending and economic growth in Malaysia : an empirical study - Tang, T.C. (Institute For Development Studies Sabah (IDS), 2000)
The major concern of this paper is to determinate the causal relation among commercial banks lending and economic performance in a small open economy, Malaysia. Engle-Granger (1987) cointegration and causality methodology were used in analysis. Annual data from 1959 to 1998 reveals a long run relationship among Real Gross Domestic Product (RGDP) and commercial banks lending in aggregate level. The long run elasticity of commercial banks lending on RGDP is 0.50 and 2.0 of RGDP on commercial banks lending. The causality analysis shows that the aggregate growth of commercial banks lending has no predictive content for economic growth. A reverse direction of causality was found there are economic growth do 'cause' growth of commercial banks lending. These results therefore imply a remarkable need of commercial banks credit while economic growth is well performed.